(untitled) (Psychology Travelogs, 2024)
The article is devoted to the study of the influence of mediation as a means of overcoming conflicts in student youth. The work analyzes the features of conflict interaction in the student environment. The nature of student conflicts is multifaceted and can be both constructive, contributing to the development of relationships and the adoption of well-founded decisions, and destructive, hindering effective interaction. This period is characterized by a heightened sense of self-esteem, maximalism and categorical moral criteria. It was found that students are very prone to the constant risk of participating in conflicts due to the daily large number of communications and the specifics of the educational process. One of the most effective ways to resolve conflicts in the student environment is mediation. The process of forming and developing the skills of a person as a mediator is considered in the context of the integrity of personal and professional growth. As a prerequisite for the development of good mediation skills, such qualities as flexibility of behavior and thinking, the ability to manage one’s emotions, the ability to ask the right questions in time, and make constructive suggestions were highlighted, which also requires analytical thinking and a high level of erudition. Assertiveness is highlighted as a personal quality of an individual for the development of good mediation skills of young people. The main types and principles of the mediation process are described. The principles on which mediation is based are determined: voluntariness, neutrality, impartiality, independence, confidentiality, self-determination and equality of rights of the parties to mediation. The results of an empirical study of the level of conflictological competence and an assessment of the significance of the characteristic features of competent conflict resolution and a study of the level of assertiveness in student youth are presented. The effectiveness of the training program for the development of mediator skills and conflict resolution in the student environment is statistically proven.